A review of the knowledge and conservation of the Burrowing Owl Athene cunicularia in Peru - Pulido, Víctor (2021)
The Burrowing Owl, Athene cunicularia, is distributed from Canada to Tierra del Fuego in America. It occupies a wide variety of natural habitats, urban-rural environments, and agro-ecosystems. Three subspecies reside in Peru: A. c. nanodes (Berlepsch and Stolzmann, 1892), A. c. juninensis (Berlepsch & Stolzmann, 1902) and A. c. cunicularia (Molina, 1782). The present work constitutes a bibliography review, supplemented with our own data, to identify the current state of knowledge about the biology and conservation status of A. cunicularia; with special emphasis on the populations that inhabit Peru.